The study of the history of Ukraine in the scientific and bibliographical activities of F. E. Petrun - Є. В. Савельєва (Vìsnik Odesʹkogo Nacìonalʹnogo Unìversitetu: Bìblìotekoznavstvo, Bìblìografoznavstvo, Knigoznavstvo, 2014)
The article deals with the scientific and bibliographical activities of the lecturer of the Odessa University, the specialist in regional history F. E. Petrun. In the 1920s he used to work in the Central Scientific Library in Odessa. F. E. Petrun’s contribution to the history and cartography of Ukraine are traced by the author of the article.